(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The agriculture sector is undergoing a technological revolution in order to cope with various emerging challenges like food insecurity, resource scarcity, climate variability, and environmental degradation. Traditional agricultural systems based on random usage of agricultural inputs and laborious farming practices are becoming less sustainable in the face of changes in climatic and socio-economic environments. Precision agriculture is defined as a technology-based and site-specific approach in agriculture, which is based on the application of digital technologies for crop cultivation while making the optimal use of natural resources. Unmanned aerial vehicles (drones) and intelligent sensor systems are some of the modern agricultural technologies. Multispectral, hyperspectral, thermal and RGB imaging technologies allow drones to instantly assess plant health, incidence of pests and diseases, nutrient deficiencies, weed problems, watering needs, and yield estimates. At the same time, various sensors in soils and environment measure important parameters such as soil moisture, nutrient content, temperatures, humidity, soil pH, and electrical conductivity. Combining all the above technologies with GIS, GPS, AI, ML, and IoT provides precise and automated agricultural interventions tailored to individual plots that increase production, decrease costs, optimize resource use, and minimize negative impacts on the environment. In this review paper, an in-depth evaluation of the concepts behind precision agriculture, types and functioning of drone technology and sensors, usage of drones in agriculture, advantages of drones in agriculture in terms of economy and environment, limitations of using drones in agriculture, and future directions for research are done. In addition to that, current status, policies related to precision agriculture, and adoption of precision agriculture in India and elsewhere are elaborated upon.